KEWENANGAN HAK UJI MATERIL PADA MAHKAMAH AGUNG RI - Enrico Simanjuntak (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2013)
Under art 24A(1) of the Constitution, the Supreme Court is granted the power to review legal instruments below laws (undang-undang). This means that an applicant could seek judicial review of regulations other than Acts of Parliament (Undang-Undang) with a request to strike it out because, for example, it contravenes national laws. This would provide the courts with an opportunity to review the legitimacy of the regulation and determine whether it is ultra vires, or beyond power. The Supreme Court has the power to cancel a regulation if it is found to be in conflict with a higher law. This article analyses the judicial review in the Supreme Court. It begins by highlighting the origins and formation of judicial review before the regulation promulgation of the Supreme Court (PERMA) No. 1/1993, and then examines several aspects of procedural law in the current Supreme Court Regulation in No. 1/2011. Keywords: Supreme Court, Judicial Review, Procedural Law.